Electrochemical performance of high and medium entropy oxides for lithium batteries - Fracchia, M.; Callegari, D.; Coduri, M.; Anselmi-Tamburini, U.; Manzoli, M.; Quartarone, E.; Ghigna, P. (Frontiers in Energy Research, 2022)
Various high and medium entropy oxides with rock salt structures were prepared and studied as anodes for lithium batteries. All the systems had complex reaction mechanisms involving conversion reactions. Their capacity and reduction potential depend on the number of components and microstructure of the initial materials. However, the dependence is difficult to rationalize based on simple stability logic. This paper discusses the implication of our findings in the wider context of the science of high entropy materials.